Managing the mixed economy: The necessity of welfare policy - Williams, Michael; Reuten, Geert (School of Management Working Papers, 1991)
It is argued that welfare policy is a necessary component of the state's actlv1tles in contemporary mixed economies. This tends to be lost sight of in the accounts not only of welfare economics and the 'new political economy', but also that of Marxist state theory. The necessity of welfare policy (and its interconnection with economic policy) emerges from the conflict-ridden interaction between a state based on (endogenously defined) right and the imperatives of the capitalist economy. The mutual interdependence of the state and the economy is analyzed in terms of the contradictory requirements of separation and intervention.